SOBORNIST’ (INTEGRITY) OF INDEPENDENT UKRAINE: DISINTEGRATION FACTORS AND ATTEMPTS OF THE SOCIAL CONSOLIDATION IN THE HISTORIC PERSPECTIVE - Адамович, С. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article analyses disintegration risks and consolidation efforts of the state bodies and the society in the process of gaining and development of Ukraine’s independence. The author argues that in the late 1980s –early 1990s, the regional differences in the country were politicized by the communist party’s structures while the political consolidation of the society since independence gaining was slowed down by the social-economic crisis and elites’ inability to introduce reforms aimed at the country’s integrity.